Physicochemical properties, digestibility and anti-osteoporosis effect of yak bone powder with different particle sizes. (July 2021) - Qin, Xiaojie; Shen, Qingshan; Guo, Yujie; Li, Xia; Liu, Jiqian; Ye, Mengliang; Wang, Hang; Jia, Wei; Zhang, Chunhui
Graphical abstract: Highlights: Size reduction of YBP promoted protein digestion instead of Ca 2+ and P 5+ release. The anti-osteoporosis effect of YBP involved B-ALP, OCN, S-CTX, ES and TRAP. No relationship between YBP size and its anti-osteoporosis efficiency was observed. Abstract: As a kind of promising resource, animal bone has been widely processed into functional foods. However, there is little research about the effect of particle size on the physicochemical properties and digestibility of yak bone powder (YBP), as well as its anti-osteoporosis activity. In this study, the YBP with median particle sizes (MPS) ranging from 19.68 to 128.37 μm were prepared, and their digestibility and anti-osteoporosis activity were investigated. The results showed that smaller MPS significantly increased water holding capacity and protein solubility without changing composition. The MPS reduction greatly promoted protein digestion, producing more peptides<3 kDa and free amino acids while decreased Ca 2+ and P 5+ release during gastrointestinal digestion. The in vivo results revealed the positive effect of YBP on ovariectomy-induced osteoporosis in rats. The bone mineral density of ovariectomized (OVX) rats was obviously improved by regulating bone turnover markers (B-ALP, OCN, S-CTX, ES and TRAP), thus potentially shedding light on osteoporosis remission. However, different MPS exhibited a weak effect on osteoporosis in OVX rats. Therefore, YBP could be produced in relatively large particle size without sacrificing food sensory quality, the processing time of which could also be shortened for higher productivity and lower cost.